2005
DOI: 10.1177/230949900501300119
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Cemented or Uncemented Femoral Component in Primary Total Hip Replacement? A Review from a Clinical and Radiological Perspective

Abstract: mid-term, cemented femoral component is recommended. However, a long-term randomised trial combined with a large cohort study or registry is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Guidelines published by NICE in the year 2000 argue that there is 'currently more evidence of the long term viability of cemented prostheses, which, in many cases, occupy the lower end of the range of prostheses cost, than there is for uncemented and hybrid prosthesis' (National Institute for Health and Clinical Excellence, 2000). However, other studies claim that cemented hips have proved to be superior only in short-term medical outcomes and that evidence is lacking for their superiority over the long term (Ni et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines published by NICE in the year 2000 argue that there is 'currently more evidence of the long term viability of cemented prostheses, which, in many cases, occupy the lower end of the range of prostheses cost, than there is for uncemented and hybrid prosthesis' (National Institute for Health and Clinical Excellence, 2000). However, other studies claim that cemented hips have proved to be superior only in short-term medical outcomes and that evidence is lacking for their superiority over the long term (Ni et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We have conducted this comparison based on several research papers comparing the outcome of cemented versus uncemented arthroplasty. A detailed literature review, conducted by Ni et al [68], compared cemented and uncemented THA in terms of bone remodeling, pain, thigh pain, quality of life, micromotions, etc. In terms of bone remodeling, for the midterm period (2-1 Oyr after operation), they concluded that cemented THA is identical to uncemented one.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…In particular, the enhanced mechanical properties and bioactivity on the nanoscale can be well suited for clinical applications [7]. Our group has developed strontium-containing bioactive bone cement for vertebroplasty [8] which has low monomer toxicity, low setting temperature and stimulates bone growth in the bone cement-bone interface.…”
Section: Introductionmentioning
confidence: 99%